Differential levels of soybean resistance to the whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) under controlled and uncontrolled environments are associated with plant age, damage intensity, and trichome density (Bioscience Journal, 2023)
Whiteflies are a severe threat to soybean production in the tropics. This study aimed to evaluate the soybean resistance level of the whitefly Bemisia tabaci in controlled and uncontrolled environments that is associated with plant age, damage intensity, and trichome density. The research was conducted under two conditions: non-sprayed (NS) and sprayed (SP). This study used 50 soybean genotypes arranged in a randomized block design with three replicates. The whitefly population was derived from natural infestations. The results showed that the highest wild population of B. tabaci occurred at 40 days after planting (DAP), i.e., 126.08 adults/plant in the NS environment and 22.57 adults/plant in the SP environment. The peak damage intensity occurred at 50 DAP, 20.71% in the NS environment, and 17.15% in the SP environment. In the NS environment, there were six resistant genotypes (including the resistant control G100H), 25 moderate, and 19 susceptible genotypes. In the SP environment, 19 genotypes were resistant, 22 genotypes were moderate, and nine genotypes were susceptible, respectively. Six soybean genotypes showed consistent resistance to B. tabaci in NS and SP environments. The low density of leaf trichomes in soybean may influence the high resistance to B. tabaci. The resistant genotypes identified in this study could be utilized in breeding programs for B. tabaci resistance.